2021
DOI: 10.1111/ijac.13914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metallization temperature on brazing joints of SiC ceramics and 2219 aluminum alloy

Abstract: A two-step process involving, the pre-metallization of the SiC ceramic by Ag-Cu-Ti foil and the Al based filler alloy was developed to join 2219 aluminum alloy and the metallized SiC. The composition of metallized SiC layer was investigated. The effect of metallization temperature on the microstructure and mechanical properties of the joint was analyzed. The brazing process showed that Al from the brazing filler and 2219 substrate reacted with Ag-Cu-Ti alloy to form intermetallic compounds. Al 3 Ti, Al 2 Ag an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…It could be observed that the addition of B 4 C had a great influence on the microstructure of the joints. Cracks appeared in the base material SiC side of the joint without the addition of B 4 C as shown our previous study, 24 whereas no obvious defects were found in the brazing seam with 1 wt.% B 4 C addition as shown in Figure 10A,D. The B 4 C aggregate zone was formed in the brazing seam.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…It could be observed that the addition of B 4 C had a great influence on the microstructure of the joints. Cracks appeared in the base material SiC side of the joint without the addition of B 4 C as shown our previous study, 24 whereas no obvious defects were found in the brazing seam with 1 wt.% B 4 C addition as shown in Figure 10A,D. The B 4 C aggregate zone was formed in the brazing seam.…”
Section: Resultssupporting
confidence: 80%
“…There are some cavities in the brazed seam with the metallization temperature of 960°C, the connection between 2219 aluminum alloy and the metallization layer is poor. A certain content of compounds with low thermal expansion coefficient could relieve the residual stress 24 . However, the reaction in the joint is violent at the higher metallization temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its intermediate thermal expansion coefficient, which lies between that of copper and silicon carbide, makes it conducive for mitigating thermal stress-induced delamination at the substrate-interface interface [24]. The novelty of this work is the evaluation of another adhesive layer Cr for the growth of nanotwins on the SiC chips, in contrast to the traditional Ti adhesive film which has been concerning due to the formation of TiC precipitates at the SiC/Ti interface, leading to an increase of the electrical resistance [25].…”
Section: Introductionmentioning
confidence: 99%